‘Break the Silence’: a tool in enhancing English presentation skills among second language learners - C. Alih, Nur Ashiquin; Komarudin, Nabila Eizati; Fakhruddin, Siti Syairah; Subramaniam, Shabina Kumari; Hussin, Anealka Aziz (Universiti Teknologi MARA, 2025)
Proficiency in delivering oral presentations is one of the most crucial skills students are expected to develop throughout their educational journey. However, previous research has shown that oral presentation tasks are typically difficult for second language learners to complete. Some of the many reasons for this difficulty experienced by learners during oral presentations were forgetting what to say, and not being confident talking in public. Hence, ‘Break the Silence’ is an innovation tool developed to assist students in structuring their oral presentation, specifically in informative speech. It offers a distinct advantage through presentation phrases tailored to specific topics useful for structuring students’ thoughts in oral presentation. This study aims to i) explore students’ perceptions regarding the usability of ‘Break the Silence’ as a learning tool; and ii) investigate students’ perceptions on the influence of ‘Break the Silence’ to enhance their oral presentation. 12 students from Universiti Teknologi MARA were chosen to try the ‘Break the Silence’ tool and share their experiences from using it. Findings revealed that students demonstrated a positive outlook on the usage of ‘Break the Silence’ as a learning tool. With its interactive features, the tool is easy to be used and navigation is not an issue for students. The study also discovered that the tool has managed to assist students in structuring their presentation and boost their confidence in speaking. It is envisioned that the ‘Break the Silence’ will continue to provide support to students in delivering an effective oral presentation.